Migration Patterns of Peripherally Inserted Central Venous Catheters at 24 Hours Postinsertion in Neonates - Srinivasan, Hari B.; Tjin-A-Tam, Ansel; Galang, Rupernina; Hecht, Alan; Srinivasan, Gopal (American Journal of Perinatology, 2013)
Objective Migration of peripherally inserted central venous catheters (PICCs) is known to happen in neonates with changes in position of the upper limb. The aim of this study is to document the migration pattern of PICCs at 24 hours postinsertion, while controlling for arm position.Study Design This was a single-centered prospective study of 100 consecutively placed PICCs in a level III neonatal intensive care unit (NICU). All PICCs were inserted by one of two certified NICU nurses in either upper or lower limb. An X-ray was obtained immediately after insertion and again at 24 hours postinsertion; both were reviewed by a single pediatric radiologist.Results Of the PICCs placed in basilic veins, 35.5% migrated toward the heart, 14.5% migrated away from the heart, and 50% did not change in position. Of the PICCs placed in cephalic veins, 21% migrated toward the heart, 15.7% migrated away from the heart, and 63.3% did not change in position. None of the PICCs placed in the saphenous veins migrated.Conclusion After controlling for arm position, 47% of PICCs placed in the upper limb migrated at 24 hours postinsertion with 32.6% migrating toward the heart. We recommend a follow-up X-ray at 24 hours postinsertion for all catheters placed in the upper limb.
Keywords: peripherally inserted central catheter; migration; cardiac tamponade; arm position